Report: Proposed interior design scheme of specialized retail for Hasbro at Ipoh Parade, Level 3, No. 20 Lot 105, Jalan Sultan Abdul Jalil, 30350 Ipoh, Perak Darul Redzuan, Malaysia / Norhafiz Kasmani - Kasmani, Norhafiz (Faculty of Architecture, Planning and Surveying, 2011)
This project is about Preposed for Specialized Retail for Hasbro Entertainment. This project aims to sell goods produced products from the company Hasbro. Hasbro Company is famous for its production of children's toys and adolescence, where many products are divided as Hasbro Toys, Games, Action Figures, Board Games, Digital Games, Online Games, and more. Hasbro also makes a sponsoring company in terms of entertainment like movie sponsorship Transformers, Toys Story, Incredible Hulk, Iron Man, Captain America and many more. Product Hasbro are on sale in shops selling toys alone and just focus on selling the concept of selling toys. The objectives of the project is to provide a new specialized retail for Hasbro and further develop the concept, proposed a more organized space, adding a special service, adding to the welcoming conceptual and provide more convenience to every customer.